2015
DOI: 10.1111/php.12402
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Triplet State of a 4‐Amino‐7‐Nitrobenzofurazan Derivative in Cyclohexane

Abstract: The nitrobenzofurazan (NBD) moiety has gained tremendous popularity over the last decades due to its fluorogenic nature. Indeed, upon interaction with aliphatic amines, it generates a stable fluorescent adduct, which has been used for protein and lipid labeling. In fact the 4-amino substituted NBD belongs to the broad family of intramolecular charge transfer molecules, with the amino group acting as an electron donor upon photoexcitation, and the nitro group as an electron acceptor. Although the singlet excite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
(108 reference statements)
1
5
0
Order By: Relevance
“…This hypothesis is also in good agreement with the inefficient intersystem crossing to the excited triplet state reported for ABF derivatives, unless than in very non polar solvents ( i. e . cyclohexane) . The identical nature of the photoproduct observed under both aerobic and anaerobic conditions, is in good agreement with the formation of the anilinyl radical as logical key intermediate after the loss of NO via homolytic N‐NO cleavage.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…This hypothesis is also in good agreement with the inefficient intersystem crossing to the excited triplet state reported for ABF derivatives, unless than in very non polar solvents ( i. e . cyclohexane) . The identical nature of the photoproduct observed under both aerobic and anaerobic conditions, is in good agreement with the formation of the anilinyl radical as logical key intermediate after the loss of NO via homolytic N‐NO cleavage.…”
Section: Resultssupporting
confidence: 80%
“…Finally, unless in very nonpolar solvents ( i. e . cyclohexane), ABF derivatives do not effectively populate the lowest triplet state after excitation with light, precluding the formation of singlet oxygen and consequently avoiding undesired intra‐ and intermolecular oxidation processes. These spectroscopic and photochemical properties combined with the derivatization through straightforward synthetic procedures, have made ABF derivatives very suited for biological labelling as well as a fluorescent sensors for the detection of reactive oxygen species…”
Section: Resultsmentioning
confidence: 99%
“…2A,B (see Methods and Materials). The excitation rate was calculated by k 01 = σ ⋅Φ exc , with an excitation cross section of σ = 8.6 ⋅ 10 −17 cm 2 36,39 and where Φ exc is the excitation photon flux. The triplet relaxation rate, k T , was allowed to vary freely for each curve, the intersystem crossing rate, k isc , was determined as a linear function of [O 2 ], while k ox and k red were set as global variables.…”
Section: Resultsmentioning
confidence: 99%
“…[110] This result is substantiated by our recent study where we showed another ICT complex to have a triplet state solely in non-polar environments. [37] Furthermore, we were the first to demonstrate the DNA binding mode of a molecule affects its ability to react with 1 O 2 . [111] Similarly, the extent of 1 O 2 generation by berberine and palmatine is dependent on the DNA sequence.…”
Section: Dna-engineered Photosensitizersmentioning
confidence: 99%
“…1), where E ox (receptor) and E red (reporter) are the oxidation potential of the receptor (electron donor) and the reduction potential of the reporter (electron acceptor), respectively, E 00 (reporter) is the energy of the S 0 to S 1 transition of the fluorophore, and C corresponds to the coulombic attraction energy experienced by the ion pair following the electron transfer reaction. In our case, the oxidation potential of phenol (+0.5V vs. SHE), [36] the reduction potential of NBF (-1.49V vs. SHE, acetonitrile) [37] and the energy of its singlet excited state (E 00 = 57.60 kcal mol -1 , acetonitrile) [37] have to be known. For NBFhd, a free energy G PeT of -11.52 kcal mol -1 is obtained, suggesting a spontaneous transfer of electron between the phenolic moiety and the NBF fluorophore.…”
Section: Photoinduced Electron Transfer (Pet)mentioning
confidence: 99%